Pronunciation, Prosody, and Intonation in Teaching Arabic, An Applied Phonology Approach - Habsah Habsah; Endri Safrudin; Maman Supriatman; Iis Susiawati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study is motivated by the low proficiency in pronunciation, prosody, and intonation in Arabic language learning due to differences between the phonological systems of the native language and the target language. Phonological errors not only affect the clarity of speech but can also alter meaning. Therefore, this study aims to examine how applied phonology is implemented and its effectiveness in improving speech accuracy and reducing phonological errors. This research employs a descriptive qualitative approach using observation, audio recordings, as well as pre-test and post-test techniques involving beginner to intermediate-level students. The data were analyzed comparatively and further validated by phonology experts. The results indicate that the application of applied phonology through articulation training, drilling methods, audio media, and acoustic analysis significantly improves pronunciation accuracy, enhances prosody, and refines intonation. In addition, there is a reduction in errors caused by native language interference. This study contributes to the development of a more systematic, effective, and applicable phonology-based model for teaching Arabic